2007
DOI: 10.1021/jp066660t
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Polycyclic Aromatic Hydrocarbons on Water and Ice Surfaces

Abstract: Laser-induced fluorescence detection was used to measure photolysis rates of anthracene and naphthalene at the air-ice interface, and the kinetics were compared to those observed in water solution and at the air-water interface. Direct photolysis proceeds much more quickly at the air-ice interface than at the air-water interface, whereas indirect photolysis due to the presence of nitrate or hydrogen peroxide appears to be suppressed at the ice surface with respect to the liquid water surface. Both naphthalene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
211
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(252 citation statements)
references
References 69 publications
35
211
4
2
Order By: Relevance
“…Donaldson and coworkers compared the air-ice and airwater interfaces using Raman spectroscopy at glancing angle of the OH-stretch bands. The protonation of acridine, an organic fluorescent pH probe, at the air-ice interface was observed in the presence of HNO 3 or HCl deposited to the ice surface from vapors (Kahan et al, 2007;Wren and Donaldson, 2012). However, no enhancement in the proton concentration was observed at the interface upon freezing mildly acidic or neutral solutions.…”
Section: Frozen Aqueous Solutionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Donaldson and coworkers compared the air-ice and airwater interfaces using Raman spectroscopy at glancing angle of the OH-stretch bands. The protonation of acridine, an organic fluorescent pH probe, at the air-ice interface was observed in the presence of HNO 3 or HCl deposited to the ice surface from vapors (Kahan et al, 2007;Wren and Donaldson, 2012). However, no enhancement in the proton concentration was observed at the interface upon freezing mildly acidic or neutral solutions.…”
Section: Frozen Aqueous Solutionsmentioning
confidence: 97%
“…These have been suggested to affect the shape of measured adsorption isotherms, e.g., for formic and acetic acids Symington et al, 2010), as well as ethanol and acetone (Abbatt et al, 2008;Starr et al, 2011). For aromatics, selfassociation of naphthalene and anthracene at the gas-ice interface has been suspected from spectroscopic investigations (Kahan and Donaldson, 2007 and supported by molecular dynamics investigations (Ardura et al, 2009). In a joint experimental and theoretical study (Heger et al, 2011), the adsorption of two 1-methylnapthalene molecules to hexagonal ice, as a model of artificial snow, was simulated at 77 K and 239 K using classical molecular dynamics.…”
Section: Molecular-level Picturementioning
confidence: 99%
“…Donaldson and co-workers [3][4][5][6][7][8] have shown that glancingangle Raman spectroscopy is a very useful surface-selective technique for probing a surface region with a thickness of the order of 10-100 molecular layers, being able to measure both surface concentrations of solutes and surface depletion of solvents. Thus, for example, Wren and Donaldson 7 used glancing-angle Raman spectroscopy to study the reaction of gas-phase ozone with NaBr and NaI at the surfaces of aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments reported here do not require surface selectivity of the kind employed in the experiments of Donaldson et al, [3][4][5][6][7][8] but simply exploit the ability of Raman spectroscopy with a narrow (<0.1 mm) laser beam to obtain spectra that arise from species close to and within the interface. This limited selectivity, perhaps somewhat unexpectedly, proves to be sufficient to detect the mutual repulsion between water molecules and NO 2 molecules at the gas-liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…The initial concentration of PCBs measured after a fresh snowfall were found to decrease by about 75% within the first 96 h (k 00.01 h (1 ), after which the concentration remained steady for the next 136 h*until the next snowfall (Herbert et al 2006). As the majority of previous research on the degradation and/or loss of organic compounds in snow and/or ice was conducted on aromatic compounds (Dubowski & Hoffmann 2000;Klan et al 2003;Dolinova et al 2006;Kahan & Donaldson 2007;Ram & Anastasio 2009), a comparison of the experimental k-values (and half-lives) are compared with the k-value determined for fluoranthene in this study, shown in Fig. 2.…”
Section: Labelled Organic Compoundsmentioning
confidence: 98%